External Trade Bulletin of the ESCWA Region, 17th Issue - United Nations (United Nations, 2013)
The Bulletin includes statistical data and indicators on the international trade in goods of ESCWA member countries, based primarily on national sources, with additional material provided by secondary sources. Data presented includes summary tables on overall trade, trends and share of the region in total world trade as well as data on intraregional trade and on the direction of trade of ESCWA member countries with other countries and regions during the period 2003-2007. This bilingual publication contains information in Arabic and English.